SbCl3-catalyzed solvent-free Friedel–Crafts reaction of phenols with mandelic acids to 3-aryl benzofuran-2(3H)-ones: Synthesis of spirocyclic 2, 3-dihydrobenzofuran-2-ones. Issue 21 (1st November 2016) - Dhotare, Bhaskar B.; Choudhary, Manoj K.; Nayak, Sandip K.
ABSTRACT: A facile, SbCl3 -catalyzed, one-pot, tandem Friedel–Crafts/lactonization reaction of phenols and mandelic acids has been developed under solvent-free conditions to afford 3-aryl benzofuran-2(3 H )-ones in good to high yields (52–90%). Additionally, the utility of 3-aryl benzofuran-2(3 H )-ones is demonstrated by using them as precursors in the synthesis of a new class of spirocyclic benzofuran-2-ones using classical synthetic methodologies. GRAPHICAL ABSTRACT: